Clinical features and prognostic factors of listeriosis: the MONALISA national prospective cohort study. Issue 5 (May 2017) - Charlier, Caroline; Perrodeau, Élodie; Leclercq, Alexandre; Cazenave, Benoît; Pilmis, Benoît; Henry, Benoît; Lopes, Amanda; Maury, Mylène M; Moura, Alexandra; Goffinet, François; Dieye, Hélène Bracq; Thouvenot, Pierre; et al.
Summary: Background: Listeriosis is a severe foodborne infection and a notifiable disease in France. We did a nationwide prospective study to characterise its clinical features and prognostic factors. Methods: MONALISA was a national prospective observational cohort study. We enrolled eligible cases declared to the National Reference Center for Listeria (all microbiologically proven) between Nov 3, 2009, and July 31, 2013, in the context of mandatory reporting. The outcomes were analysis of clinical features, characterisation of Listeria isolates, and determination of predictors of 3-month mortality or persisting impairment using logistic regression. A hierarchical clustering on principal components was also done for neurological and bacteraemic cases. The study is registered atClinicalTrials.gov, numberNCT01520597 . Findings: We enrolled 818 cases from 372 centres, including 107 maternal–neonatal infections, 427 cases of bacteraemia, and 252 cases of neurolisteriosis. Only five (5%) of 107 pregnant women had an uneventful outcome. 26 (24%) of 107 mothers experienced fetal loss, but never after 29 weeks of gestation or beyond 2 days of admission to hospital. Neurolisteriosis presented as meningoencephalitis in 212 (84%) of 252 patients; brainstem involvement was only reported in 42 (17%) of 252 patients. 3-month mortality was higher for bacteraemia than neurolisteriosis (hazard ratio [HR] 0·54 [95% CI 0·41–0·69], p<0·0001). For both bacteraemia and neurolisteriosis, the strongest mortality predictors were ongoing cancer (odds ratio [OR] 5·19 [95% CI 3·01–8·95], p<0·0001), multi-organ failure (OR 7·98 [4·32–14·72], p<0·0001), aggravation of any pre-existing organ dysfunction (OR 4·35 [2·79–6·81], p<0·0001), and monocytopenia (OR 3·70 [1·82–7·49], p=0·0003). Neurolisteriosis mortality was higher in blood-culture positive patients (OR 3·67 [1·60–8·40], p=0·002) or those receiving adjunctive dexamethasone (OR 4·58 [1·50–13·98], p=0·008). Interpretation: The severity of listeriosis is higher than reported elsewhere. We found evidence of a significantly reduced survival in patients with neurolisteriosis treated with adjunctive dexamethasone, and also determined the time window for fetal losses. MONALISA provides important new data to improve management and predict outcome in listeriosis. Funding: Programme Hospitalier Recherche Clinique, Institut Pasteur, Inserm, French Public Health Agency.